Molecular characterization of leaf spot caused by Alternaria alternata on buttonwood (Conocarpus erectus L.) and determination of pathogenicity by a novel disease rating scale. - Muhammad Fahim Abbas (Public Library of Science (PLoS), 2021)
The buttonwood (Conocarpus erectus L.) is a mangrove shrub belonging to Combretaceae family. It mostly grows on the shorelines of tropical and subtropical regions in the world. It was introduced to Lasbela University of Water, Agriculture & Marine Sciences (LUWMS), Uthal, Baluchistan as an ornamental plant as it grows well under harsh, temperate and saline conditions. During a routine survey, typical leaf spot symptoms were observed on the leaves of buttonwood plants. A disease severity scale for alternaria leaf spot of buttonwood was developed for the first time through this study. Disease severity according to the scale was 38.97%. The microscopic characterizations was accomplished for the identification of Alternaria alternata and Koch's postulates were employed to determine the pathogenicity. For molecular identification, 650 bp internal transcribed spacer (ITS) regions (ITS1, 5.8s and ITS2) were amplified from three representative isolates (LUAWMS1, LUAWMS2 and LUAWMS3) through polymerase chain reaction (PCR). The nucleotide sequences from ITS regions of the isolates were submitted to NCBI with GenBank accession numbers MW585375, MW585376 and MW585377, respectively. The phylogenetic tree of 22 A. alternata isolates was computed and representative isolates exhibited 99.98% genetic similarity with mangroves ecosystem isolates. This study reports the incidence of alternaria leaf spot of buttonwood at LUWMS for the first time. It is suspected that the disease may spread further. Therefore, effective management strategies should be opted to halt the further spread of the disease.